TRANSRECTAL BIOPSY OF PROSTATE: IS IT OUR PAST, PRESENT AND FUTURE? - Khudaybergenov U.A; Ollayorov A.A; Shomarufov A.B; Kasimov S.S (The Bioscan, 2024)
Among diagnostic tools for the early detection of prostate cancer, transrectal biopsy of the prostate has emerged as a pivotal procedure, allowing clinicians to obtain tissue samples for pathological examination and subsequent treatment planning. This comprehensive literature review aims to delve into the historical evolution, current practices, complications, complication solutions, and future perspectives of transrectal prostate biopsy, synthesizing findings from a wide range of studies and contributing to the ongoing discourse in urological oncology.